Lexical Historical of the Kazakh and Altai languages (Eurasian Journal of Philology Science and Education, 2016)
In article lexical, phonetic, grammatical similarities and differences of related Altai language which treats the kipchak-Kyrgyz subgroup of kipchak group of Turkic languages which decreased quantity of the speaking now are compared. In article the history of development of the Altai language is given in this chronology the Early Turkic era (VI, VIII-XIIVV), the Mongolian era (XIII-XVII вв), the Russian colonial era (the beginning of the XVIII-XX century), the Era after a great Kazan socialist revolution and the Oyrot era (an era of foundation of the Altai autonomous region). In the alphabet of the Altai language 37 sounds are described, 12 of them are vowels, 23 consonants and are peculiar to it 4 sounds: J ј, Ӱӱ, Ӧӧ, Ҥҥ are also described signs which don’t give a certain value as Ь,Ъ. In article in the form of the table the lexical structure of the Altai language which gives a lexical meaning of words which give information on the general Turkic archaic words is compared to the Kazakh language. For example related relations, body organs, house accessories. In the Altai language influence of political superiority of Mongols and Russians is specified, besides the border of loan words with Mongolian, kalmak and tungis– manchur, Russian is defined.
Keywords: Turkic languages; the lexical composition; loan words; historical vocabulary